2022
DOI: 10.3389/fonc.2022.777934
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognosis and treatment decisions for patients with second primary lung cancer following esophageal cancer

Abstract: IntroductionAs the long-term prognosis of esophageal cancer (EC) is improving, concerns of a second primary malignancy (SPM) have increased. However, research on lung cancer as the SPM after EC is limited. Therefore, we aimed to explore the prognostic factors and clinical treatment decisions of patients with second primary lung cancer following esophageal cancer (SPLC-EC).Materials and methodsWe identified the data of 715 patients with SPLC-EC from the Surveillance, Epidemiology, and End Results (SEER) databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Based on these factors, nomogram prediction models for CRA are constructed for both patient groups, demonstrating good prediction efficiency and clinical practicality. Previous studies have shown that serum iron levels are negatively correlated with tumor staging and positively correlated with patient prognosis in lung cancer cases, 25 as the incidence of CRA in lung cancer patients tends to increase with later stages of cancer and lower levels of serum iron due to tumor cell proliferation and increased demand for iron. Malignant tumors are consumptive diseases, and with the progression of the disease, some patients with advanced lung cancer consume more in the body because of the deterioration of malignant fluid, which leads to the decrease in serum iron content of hematopoietic raw materials, thus leading to CRA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these factors, nomogram prediction models for CRA are constructed for both patient groups, demonstrating good prediction efficiency and clinical practicality. Previous studies have shown that serum iron levels are negatively correlated with tumor staging and positively correlated with patient prognosis in lung cancer cases, 25 as the incidence of CRA in lung cancer patients tends to increase with later stages of cancer and lower levels of serum iron due to tumor cell proliferation and increased demand for iron. Malignant tumors are consumptive diseases, and with the progression of the disease, some patients with advanced lung cancer consume more in the body because of the deterioration of malignant fluid, which leads to the decrease in serum iron content of hematopoietic raw materials, thus leading to CRA.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] A retrospective study of a large cohort of patients with a history of invasive breast cancer revealed that 5.34% of the patients developed malignant pleural and/or pericardial fluid as the first clinical sign of distant metastasis. [33] The pericardium is not the preferred site of metastasis in breast cancer, and pericardial metastasis develops in only 19% of cases. Approximately 12 to 25% of breast cancer cases with pericardial metastasis have pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Since most cases do not present clinically, they are not diagnosed until autopsy. [34][35][36] Involvement of the peritoneal surfaces, which is another serosal involvement of breast cancer, is a rare clinical manifestation that usually occurs during progressive progression or is much less frequently detected at the initial diagnosis. The most common diagnostic finding is diffuse peritoneal thickening and ascites development.…”
Section: Discussionmentioning
confidence: 99%
“…As the incidence of SPMs increases signi cantly, recent developments in SPMs have heightened the need for research on the monitoring, prognosis, and treatment decisions for clinical and public health [20,21].…”
Section: Discussionmentioning
confidence: 99%